LA ORTOGRAFÍA EN EL AULA - Ríos González, Gabriela (2013)
Many times we listen to teachers of School, High-school, and even college complain about "spelling mistakes" theirstudents have. In this article I make a presentation on some problems faced by teachers to teach spelling and later dosome didactical recommendations to address it in a more playful and enjoyable for students.